DISCOURSE ANALYSIS OF “TITANIC” MOVIE THEME SONG - Rosmita Ambarita; Vera Kristiana; Diana Sopha; Harianto II Harianto II (Fakultas Sastra UMN AL Washliyah, 2022)
The researcher made this paper based on my discourse analysis to the song “My Heart Will Go On” as the theme of Titanic. It was interesting to analyze this song because the researcher really like the movie (Titanic) of which this song’s as the theme. The objective of this research was to know what the main idea or information from this song whether it is appropriate with the story of this movie or not. It was a descriptive qualitative method and it used the semantic approach to analyze the song lyrics. In order the researcher can understand the meaning of the song easily, first, translating the song lyrics into Indonesian, then trying to understand the meaning of each word in this song, next, analyzing the social and cultural context of the song. The researcher also tried to give a personal response to the song based on opinion to the movie generally and to the song specifically. It is a good song. This song is really about true love. The Titanic movie gave people a stereotype every time listened to this song they would imagine that the song is from Rose for jack, her true love. The content of this song is all about love. Love did not disappear although one of them was died. They would meet and see each other in her dream every night. It seems to be impossible, but it shows us what a powerful the true love is. “My Heart Will Go On” tells us the different point of view. In this song, true love can not disappear, it’s forever in her heart.